Prevalence and profile of adverse drug reactions in high-risk pregnancy: a cohort study - Kathlen Dayanne Lopes da Silva; Flávia Evelyn Medeiros Fernandes; Thiago de Lima Pessoa; Sara Iasmin Vieira Cunha Lima; Antônio Gouveia Oliveira; Rand Randall Martins (BMC, 2019)
Abstract Background Commonly used drugs in pregnant women include antihypertensives, hypoglycemic agents, analgesics, antimicrobials, antiemetics and antispasmodics but the use of medicines during pregnancy, especially in high-risk pregnancy, may be associated with high risk of adverse drug reactions (ADR). The objective of this study was to determine the risk of an adverse drug reaction in hospitalized high-risk pregnant women and the factors associated with their occurrence. Methods The study received IRB approval and all patients gave written informed consent. Observational cohort study conducted from September 2015 to November 2016 in 1070 pregnant women consecutively admitted to the high risk sector of the University Maternity Januário Cicco in Brazil. ADR were detected through daily active search. Risk factors for the occurrence of ADR were determined using multivariate logistic regression. Results The mean age of the study population was 26.2 ± 7.2 years and gestational age was 31.2 ± 7.2 weeks. The average number of previous pregnancies was 2.4 ± 1.8 and 46.4% reported cases of previous abortion/miscarriage. ADR were observed in 10.7% of women. The main medicines involved, with the incidence rate of ADR per 100 prescriptions of the drug (IR), were parenteral scopolamine (IR 14.9%), methyldopa (IR 15.9%), insulin (IR 8.46%), oral scopolamine (IR 3.58%), captopril (IR 2.38%) and ceftriaxone (IR 18.4%). Multivariate analysis showed that only gestational age in weeks (odds-ratio 0.97, 95% confidence interval 0.95-0.98) was related to the occurrence of adverse reactions. Conclusion Lower gestational age is a risk factor for high-risk pregnant women, increasing the likelihood of adverse reactions, with parenteral medications being those that have the highest potential risk of harm.